KAJIAN PENTINGNYA BELAJAR MENGEVALUASI PELAKSANAAN PEMBELAJARAN MENGGUNAKAN MODEL EVALUASI CIPP - Puja Devi Sri Raso Tampubolon; Dyoys Anneke Rantung; Lamhot Naibaho (STKIP PGRI Situbondo, 2023)
The goal of evaluating the implementation of Christian religious education in schools is to determine the extent to which lesson plans have been implemented. In the absence of learning evaluation activities in schools, teachers will be unaware of deficiencies or even issues arising from their teaching and learning endeavors. These issues, such as the lack of textbooks and instructional aids in learning activities, may prevent students from comprehending the material delivered by the instructor. In order to accomplish this, the teacher must acquire evaluation skills, which entails that he develops his capacity to conduct evaluation tasks. And this is really helpful for identifying gaps in the implementation of learning by the teacher. The CIPP evaluation model is the evaluation model that should be learned. This study aims to persuade PAK teachers to enhance their abilities to evaluate the implementation of learning and to introduce them to the CIPP evaluation paradigm. This is a result of the lack of learning evaluation activities, including PAK, conducted by teachers in schools. The method of research employed is qualitative and literature-based. This study's findings include an explanation of the scope of learning evaluation in general, the CIPP evaluation model, the relevance of evaluating PAK by instructors according to the Bible, and the considerations PAK teachers must make while utilizing the CIPP model to conduct evaluations.